Measurement of patient-reported outcomes. 2: Are current measures failing us?. (3rd June 2019) - McKenna, Stephen P.; Heaney, Alice; Wilburn, Jeanette
Abstract: All instruments designed to measure latent (unobservable) variables, such as patient-reported outcomes (PROs), have three major requirements; a coherent construct theory, a specification equation, and the application of an appropriate response model. The theory guides the selection of content for the questionnaire and the specification equation links the construct theory to scores produced with the instrument. For the specification equation to perform this role, the patient-reported outcome measure (PROM) must employ a response model that generates values for its individual items. The most commonly applied response model in PROM development is the Rasch model. To date this level of measurement sophistication has not been achieved in PRO measurement. Consequently, it is not possible to establish a PROM's true construct validity. However, the development of the Lexile Framework for Reading has demonstrated that such objective measurement is possible for latent variables. This article argues that higher quality PROM development is needed if meaningful and valid PRO measurement is to be achieved. It describes the current state of PROM development, shows that published reviews of PROMs adopt inappropriate criteria for judging their quality, and illustrates how the use of traditional PROMs can lead to incorrect (and possibly dangerous) conclusions being drawn about the efficacy of interventions.